Juridical Implication of Falsification of Signature in Minutes of Deed of Notary Position (Study of the Supreme Court's Decision Number 1234 K / Pid / 2012) - Reza Ardiyanto,S.H; Moh Saleh (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
Problems in this study, first: how is the juridical implications forged the signatures on the minutes of the deed of the Notary on the Supreme Court judgment No. 1234 k / PID / 2012? Second, how is the legal effect of the Minuta Deed falsified by a notary? This study is normative, normative legal research. The study concluded, first: implications for the post of notary can be categorized into four (4) aspects namely,i) the implications of the engagement deed, ii) Aspects of the administrative office; iii) Professional Aspects of the Membership; vi), the criminal aspect. Second, as a result of the Law of Minuta certificates were forged by a Notary which resulted in deed only has the strength of evidence as the deed under hand, if the parties could prove the authentic act proficiency level in the trial court and resulted in the deed can be canceled and the strength of evidence as the deed under hand will not apply continuing involvement.